2022
DOI: 10.1111/dom.14663
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor 15 (GDF15) and semaglutide inhibit food intake and body weight through largely distinct, additive mechanisms

Abstract: Aims: To evaluate whether the potent hypophagic and weight-suppressive effects of growth differentiation factor-15 (GDF15) and semaglutide combined would be a more efficacious antiobesity treatment than either treatment alone by examining whether the neural and behavioural mechanisms contributing to their anorectic effects were common or disparate.Materials/Methods: Three mechanisms were investigated to determine how GDF15 and semaglutide induce anorexia: the potentiation of the intake suppression by gastroint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…These data suggest that GLP-1 and GDF-15 act through distinct pathways. Interestingly, Ghidewon et al showed that dual treatment with GDF-15 and GLP-1 induces more robust weight loss in mice compared to each agent alone, proposing potential synergistic effects [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data suggest that GLP-1 and GDF-15 act through distinct pathways. Interestingly, Ghidewon et al showed that dual treatment with GDF-15 and GLP-1 induces more robust weight loss in mice compared to each agent alone, proposing potential synergistic effects [31].…”
Section: Discussionmentioning
confidence: 99%
“…Although we show that liraglutied and lorcaserin weight loss pathways are independent of GDF-15, it still remains to be fully elucidated if GDF-15 does play a role in weight regulation through other pathways. Based on studies in mice, if GDF-15 can cause appetite suppression, that could be through a) activating the GFRAL receptor located in the hindbrain [34], b) gastrointestinal malaise induction [14,31,[35][36][37][38], and/or c) efferent vagal signaling causing delayed gastric emptying [12]. As GDF-15 may act through multiple mechanisms, its combination with different weight loss pharmacological agents could potentiate their effects, as proposed by data in animal studies [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, GDF15 was used in combination with stimulating the release of satiety signals in the gastrointestinal tract of rats. It was found that the combined use of the two did not have a synergistic effect on reducing food intake [58], suggesting that GDF15 did not reduce food intake by increasing satiety.…”
Section: The Mechanism By Which Gdf15 Regulates Body Weightmentioning
confidence: 99%
“…Growth differentiation factor 15 (GDF15) is a stress-response cytokine expressed by a variety of tissues that is secreted into circulation in response to a wide array of stimuli and chronic diseases, including cancer and chemotherapy. GDF15 signaling gained significant attention after it was confirmed to be an agonist at the GDNF family receptor α-like (GFRAL)-RET complex. Previously published reports highlighted the promise of GDF15-mediated signaling via GFRAL as a potential target for the pharmacologic treatment of obesity because of its potent capacity to suppress food intake. ,, Expression of GFRAL-RET in the central nervous system (CNS) is limited to neurons in the area postrema (AP) and nucleus tractus solitarius (NTS) of the brainstem, where it provides critical contributions to energy balance and the induction of nausea and emesis. , Importantly, these two adjacent structures do not possess a functional blood–brain barrier, allowing circulating GDF15 and other agents (including systemically delivered substances) to directly reach the neurons located in the AP/NTS. , Results from several recent reports revealed that the anorectic response to GDF15 signaling was largely secondary to malaise, and as such the GDF15-GFRAL signaling pathway may be a potential target for the development of new antiemetic pharmacological agents. Most recently, Hsu et al reported that GFRAL knockout mice were insensitive to the long-term anorexia and cachexia/weight loss that typically results from the administration of cisplatin.…”
Section: Introductionmentioning
confidence: 99%